1971
DOI: 10.1115/1.3408868
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication Theory for Micropolar Fluids

Abstract: The equations governing the flow of a fluid with rigid, spherical substructure are summarized. A two-dimensional flow field is considered and applied to the geometry of a slider bearing. Order-of-magnitude arguments are used which reduce the governing equations to a system of coupled, linear, ordinary differential equations. The equations are solved subject to appropriate boundary conditions and the effects of substructure discussed with the help of a specific numerical example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(62 citation statements)
references
References 0 publications
0
62
0
Order By: Relevance
“…Many authors have assumed that special class of fluids, see Kline and Allen [9], Ahmadi [11], Allen and Kline [12], and Rees and Bassom [13].…”
Section: Solution Methodologymentioning
confidence: 99%
“…Many authors have assumed that special class of fluids, see Kline and Allen [9], Ahmadi [11], Allen and Kline [12], and Rees and Bassom [13].…”
Section: Solution Methodologymentioning
confidence: 99%
“…A number of studies [1][2][3][4][5][6][7][8][9][10] on micropolar lubrication have been reported. Das et al [11] have presented the dynamic characteristics of hydrodynamic journal bearings lubricated with micropolar fluids.…”
Section: Introductionmentioning
confidence: 99%
“…In case of Newtonian fluids it is observed that the increase in load carrying capacity, lower coefficient of friction and delayed time of approach by keeping the viscosity constant. Many investigators [13][14][15][16][17][18][19][20][21] reported that the uses of micropolar fluids in different bearing systems which results in decrease in the load carrying capacity and improve in squeeze time. In general, viscosity of all the fluids decreases with increase in temperature.…”
Section: Introductionmentioning
confidence: 99%